2018
DOI: 10.20546/ijcmas.2018.710.002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of E. coli from Bovine Mastitis and Their Antibiotic Sensitivity Pattern

Abstract: A total of 300 milk samples from buffaloes were evaluated for mastitis and incidence of E. coli. Overall, 157 milk samples (52.33%) were positive for mastitis and out of these positive isolates, 27 bacterial isolates (17.19 %) were identified as E. coli. All the 27 isolates of E. coli were tested for in vitro sensitivity towards 15 antibacterial drugs. The highest resistance was attributed towards antibiotic Kanamycin followed by Cefotaxime, Trimethoprim, Cefotaxime + Clavulanic acid, Amoxycillin, Cefixime, Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
4
4
0
Order By: Relevance
“…Regarding the antibiotic susceptibility test of E. coli and S. aureus, the result showed an emerging antibiotic resistance among both isolates. All the E. coli isolates in this study were resistant to Ampicillin which was in compliance with the findings of Badri et al (2017) [9] and Singh et al (2018) [25]. Besides ampicillin resistance, the results revealed higher resistance among E. coli towards Nalidixic acid, Tetracycline, Ceftriaxone and Ciprofloxacin in descending order.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the antibiotic susceptibility test of E. coli and S. aureus, the result showed an emerging antibiotic resistance among both isolates. All the E. coli isolates in this study were resistant to Ampicillin which was in compliance with the findings of Badri et al (2017) [9] and Singh et al (2018) [25]. Besides ampicillin resistance, the results revealed higher resistance among E. coli towards Nalidixic acid, Tetracycline, Ceftriaxone and Ciprofloxacin in descending order.…”
Section: Discussionsupporting
confidence: 89%
“…Generally, 33 (12.10%) milk samples were displayed positive results for E. coli . Similar findings were recorded by Singh et al (2018) who observed that 27 (17.19%) E. coli strains were recovered from 157 milk samples of buffalo mastitis. Several previous studies were largely similar to the current results, and the percentage of E. coli from the milk of buffaloes infected with mastitis ranged between 15 and 18% ( Ali et al, 2011 , Bhanot et al, 2012 , El-Sayed Lamey et al, 2013 ).…”
Section: Discussionsupporting
confidence: 88%
“…Incidence of streptococci (32.53%), micrococci (5.74%), Corynebacterium (1.91%), and Escherichia coli (0.95%) was reported in cases of bovine mastitis. However, recently, 17.19% mastitis cases in buffalo were due to infection with Escherichia coli [27][28][29][30][31].…”
Section: Etiology Of Mastitismentioning
confidence: 99%